Phenylacetylene hydrogenation on Au@Ni bimetallic core–shell nanoparticles synthesized under mild conditions. Issue 3 (20th January 2016) - Vysakh, A. B.; Lazar, Anish; Yadukiran, V.; Singh, A. P.; Vinod, C. P.
Abstract : The synthesis of Au@Ni bimetallic core–shell nanoparticles through an energy efficient (lower temperature) route in oleylamine following a sequential reduction strategy and their hydrogenation activity is reported. Abstract : The synthesis of Au@Ni bimetallic core–shell nanoparticles through an energy efficient (lower temperature) route in oleylamine following a sequential reduction strategy is reported. The method is found to be useful for the synthesis of a very thin nickel shell (2 nm) over a gold core (15 nm). Synergistic effects are observed in catalyzing phenylacetylene hydrogenation under different solvent conditions.